ANALISIS PELAKSANAAN PEMBELAJARAN KIMIA DI KELAS HOMOGEN (Studi Kasus Pembelajaran Kimia di SMA Negeri 11 Banda Aceh) - Haris Munandar; Jofrishal Jofrishal (Lantanida Journal, 2016)
Conceptual understanding of chemistry requires the ability to represent and interpret the problems of chemicals in a form that is easy to understand. One way that allows students to learn chemistry is to implement effective learning activities. This research was conducted in SMA Negeri 11 Banda Aceh. One of the schools with a homogeneous class management systems based on the same gender. The purpose of this study was to determine the learning process for the chemical held in a homogeneous class. Definition of homogeneous classes of this research is the class that is populated by students collectively have the same gender. Observations obtained is the percentage of teachers' activities with a percentage of 71.42% of activities, which means that activities of teachers in the classroom in both categories (51% - 80%). Results of student feedback through a questionnaire, obtained only 32% of students from a total of 88 students who find it easy to understand the chemistry lesson taught over the years, while the remaining amount to 68% of students still find it difficult to understand the chemistry lesson. Chemistry learning in homogeneous classes requires readiness of teachers, both in the preparation of learning tools and also the ability of teachers to manage the classroom, so that learning can be effective.